Reduction of microbial contamination in septic tank sludge by the process of composting effects of type of bulking agent and volume ratios of septage to bulking agent - Encarnacion, Ronnie Hernandez (2001)
This study was conducted to evaluate the feasibility of reducing microbial contaminants (i.e. fecal coliform, salmonella, and helminth eggs) in the dewatered septic tank sludge or "septage". The dewatered septage and bulking agents were c0-composted following the simple and cost-efficient windrow composting process. The dewatered septage exhibited characteristics such as high moisture content, low volatile solids, and low carbon content - parameters that are significant to composting. In addition, the septage possesses adequate nitrogen level (1.73% drb), low metal content, and reduced levels of fecal coliform (E.coli) that can be attributed to the anaerobic digestion it underwent inside the septic tank. In order to enhance the septage composting capability rice straws, sawdust, and woodchips were used as bulking agents (BA's). These bulking agents have become sufficient source of carbon (TOC>42%), high solids content and give structure to the window pile. The blending of the dewatered septage and BA's has produced a compost-blended feedstock that has the capacity of composting. However, the plastic nature of septage (moisture content - 78%) resulted to difficulty in handling the compost feedstock. Mixing ratios of 1:1, 1:2, and 1:3 on the volume basis were formulated to address the earlier concern in handling and establish a more practical approach in monitoring for microbiological destruction. Initial co-composting of the raw materials has achieved themophilic temperatures for both sawdust-septage mixtures and woodchips-septage mixture. A maximum of 42̊C was attained in the first week of composting but due to limiting factors like small windrow pile volume, atmospheric condition, and numerous voids on the set of mixture with woodschips as BA's, temperature decreased. pH likewise declined in the initial phase of composting as organic acids were produced. Fluctuations in the operating parameters such as pH, temperature, and organic matter content (TVS) were noted. Temperature values in all mixing proportions have fluctuated to ambient levels and the pH values approached 7.0 towards the end of the composting period (after 30-70 days). Sawdust and rice straws amended compost mixtures accomplished 95% reduction in fecal coliform. All compost products have passed the USEPA guidelines for pathogen reduction (Salmonella, E. coli, Helminth eggs) prior to land application. Assessment of the composting process has identified all the woodchips-septage mixture have achieved the highest reduction in combustible organic matter content (TVS-25%), fastest composting period (61 days), and a temperature of 41̊C.